Prototype of an automatic ballast system for cargo ships based on Outseal PLC - Sukran, Ilham; Yelfianhar, Ichwan (Department of Electrical Engineering Universitas Negeri Padang, 2024)
The ballast system is crucial for maintaining the stability of ships, especially cargo ships that generally still use manual systems. The weaknesses of manual systems include low efficiency, long operational times, and the potential for technical errors (human error) that can increase the risk of accidents. This research aims to develop an automatic ballast system using Outseal PLC as the control center. The process begins by activating the system through the start button. Objects are placed on the prototype, and the system's response to tilt angles is measured using a gyroscope sensor. When a tilt angle is detected, the system automatically fills the tank with water to restore stability. The volume of water entering the tank is measured using a flowmeter sensor. Test results show that when the tilt reaches 10 degrees or -10 degrees, the system automatically fills the tank with water. This process continues until all tanks are optimally filled with a volume of 450 ml, after which the system empties all tanks. The research results indicate that the system can effectively manage stability through water filling in the tanks, and the designed program functions according to the desired specifications